Leading the Charge for SoTL - Embracing Collaboration - Anita Cassard; Brian Sloboda (Park University, 2014)
The scholarship of teaching and learning (SoTL) enables colleges and universities to assess student learning and measure the outcomes by engaging in meaningful research, and to disseminate this research. The objective of this paper is to give a snapshot of and assess the current thinking behind this scholarship by presenting examples of SoTL, and to provide insights into the measurement of SoTL research by faculty members. By presenting a carefully crafted research agenda in SoTL, colleges and universities can disseminate this research as a means of providing useful assessments of student learning and measurements of relevant outcomes.